Zircon fingerprint of the Neoproterozoic North Atlantic: Perspectives from East Greenland - Olierook, Hugo; Barham, Milo; Kirkland, Chris; Hollis, Julie; Vass, A. (ELSEVIER, 2020)
Correlations across the once-contiguous North Atlantic region remain challenging, particularly for pre-Caledonian packages. Here, we present new zircon U-Pb and Hf isotope data from five metasedimentary samples and three granites from East Greenland to assess the age and provenance of Meso- to Neoproterozoic successions in this area, and to evaluate their correlatives across the North Atlantic region. Detrital zircon U-Pb data yield maximum depositional ages of 936 ± 15 Ma (2σ) that indicate the metasedimentary rocks of this region of East Greenland are probably a component of the Neoproterozoic Nathorst Land Group (lower Eleonore Bay Supergroup). Intruding granites are exclusively of Caledonian age at 426 ± 1 Ma (2σ) and contain a significant xenocrystic cargo with comparable ages to detrital zircon in the host metasedimentary sequences. Detrital zircon age components are concentrated between ca. 1850 and 920 Ma, with prominent peaks at ca. 1620 Ma, 1450 Ma and 1080 Ma, and additional subcomponents at 2900–2600 Ma (~4%) and 2030–1940 Ma (~2%). Provenance of this detritus is likely from the East Laurentian margin via axial drainage to East Greenland. Statistical analyses of a newly-compiled circum-Atlantic detrital zircon dataset corroborates a model in which sedimentation occurred in three distinct megasequences: (1) 1020–950 Ma, as a response to the opening of the Asgard Sea that followed Laurentia–Baltica collision, (2) 920–840 Ma, recording the onset of further rifting of the North Atlantic and attempted breakup of Rodinia, and (3) 740–635 Ma, concomitant with the breakup of Rodinia and ending with the Marinoan glaciation. The first two megasequences show strong U-Pb and εHf similarities in both space and time across the North Atlantic. However, there is a significant increase in detrital zircon disparity between the second and third megasequences, which we propose is associated with increased compartmentalization of depocentres with localized supply and distinct sediment routing pathways during continental breakup.